Growth, grain yield and calcium, potassium and magnesium accumulation in common bean plants as related to calcium nutrition - Lucas da Silva Domingues; Nerinéia Dalfollo Ribeiro; Jerônimo Luiz Andriolo; Micheli Thaise Della Flora Possobom; Allan Emanoel Mezzomo Zemolin (Acta Scientiarum. Agronomy, 2016)
The objective of this work was to evaluate the plant growth and grain yield characteristics and the accumulation of calcium, potassium and magnesium in the leaves and grains of common bean cultivars grown with different calcium concentrations in the nutrient solution. Two experiments were conducted with nutrient solutions in a soilless system in a greenhouse. In the first experiment, five calcium concentrations (1.10, 1.65, 2.20, 2.75 and 3.30 mmol L-1) and three common bean cultivars (Iraí, BRS Expedito and Carioca) were evaluated. Higher calcium concentrations (2.20, 2.75, 3.30, 3.85, 4.40 and 4.95 mmol L-1)and two common bean cultivars (BRS Expedito and Carioca) were tested in the second experiment. Dry mass of the shoot and root, grain yield and calcium accumulation in the leaves and grains increased linearly in common bean plants supplied with calcium concentrations between 2.20 and 4.95 mmol L-1. The high calcium concentration did not reduce the accumulation of calcium, potassium and magnesium in the leaves and grains. Common bean plants grown with high calcium concentrations present higher dry mass of the shoot and root, high grain yield and high calcium concentration in the leaves and grains.